Pajak Karbon dalam Langkah Pelestarian Lingkungan - Kalyana Mitta Kristanti; Prianto Budi Saptono (Jurnal Akuntansi Keuangan dan Bisnis, 2022)
There are three objectives in this research. The first objective is to analyze Indonesia's commitment to reducing greenhouse gas (GHG) emissions. The second objective is to examine the carbon tax regulations that have been set by the government. The third objective is to analyze the potential of a carbon tax in environmental conservation. The research method used is the descriptive qualitative method. This study elaborates on three research findings. The first research result shows that the Indonesian government has committed to reducing GHG emissions. This is stated in sustainable and environmentally friendly development activities and is on the 2020-2024 National Medium-Term Development Plan agenda. The government also stipulates laws and regulations to reduce gas emissions. The second research result elaborates that the government has passed the carbon tax regulation as an effort to accelerate climate change mitigation. Carbon tax provisions are applied to the use of carbon-containing products or activities that produce carbon emissions. The third research result explains that the determination of a carbon tax has the potential to protect the environment. Thus, the carbon tax is used to correct the social costs arising from negative externalities due to environmental pollution.